2000
DOI: 10.1067/mva.2000.105005
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for perioperative cardiac evaluation from the American College of Cardiology/American Heart Association task force are effective for stratifying cardiac risk before aortic surgery

Abstract: The ACC/AHA guidelines were effective in stratifying cardiac risk by using clinical predictors and an estimate of the physical capacity of the patient. Their use may allow a reduction in unnecessary noninvasive testing in patients stratified as being at low risk, while permitting the selection of all patients likely to benefit from preoperative coronary artery disease optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 45 publications
0
16
0
2
Order By: Relevance
“…39 Past guidelines have proven safe and effective in reducing unnecessary resource utilization. [40][41][42] The first step, prior to planned aneurysm repair, is to determine whether an active cardiac condition exists, such as an unstable coronary syndrome (unstable or severe an- • MET Ն4 (see Table IV May proceed with aneurysm repair. In patients with known cardiovascular disease or at least one clinical risk factor, beta blockade is appropriate.…”
Section: Cardiac Diseasementioning
confidence: 99%
“…39 Past guidelines have proven safe and effective in reducing unnecessary resource utilization. [40][41][42] The first step, prior to planned aneurysm repair, is to determine whether an active cardiac condition exists, such as an unstable coronary syndrome (unstable or severe an- • MET Ն4 (see Table IV May proceed with aneurysm repair. In patients with known cardiovascular disease or at least one clinical risk factor, beta blockade is appropriate.…”
Section: Cardiac Diseasementioning
confidence: 99%
“…3,31,38 Several studies found that the ACC/AHA guidelines are effective for risk stratification before surgery. [39][40][41] Inconsistent conclusions were published by authors who examined the stress test performed according to the ACC/AHA guidelines.…”
Section: Predictive Value Of the Guidelinesmentioning
confidence: 99%
“…66 The few studies that have evaluated the reliability of the ACC/AHA algorithm have limitations: they had few cardiac events; they failed to demonstrate that the algorithm is effective in stratifying cardiac risk across the 3 strata proposed in the algorithm; and they did not compare the predictive accuracy of the ACC/AHA algorithm with the most accurate clinical risk indices (i.e., the Lee and Detsky indices). 67,68 The recommendations in the ACC/AHA algorithm regarding non- …”
Section: American College Of Cardiology / American Heart Association mentioning
confidence: 99%